Antisocial and prosocial behavior in sport: The role of motivational climate, basic psychological needs, and moral disengagement - Hodge, K.; Gucciardi, Daniel (2015)
The purpose of this investigation was to examine whether the relationships between contextual factors and basic psychological needs were related to antisocial and prosocial behavior in sport. A two-study project employing Bayesian path analysis was conducted with competitive athletes (Study 1, n = 291; Study 2, n = 272). Coach and teammate autonomy-supportive climates had meaningful direct relations with need satisfaction and prosocial behavior. Coach and teammate controlling climates had meaningful direct relations with antisocial behavior. Need satisfaction was both directly and indirectly related with both prosocial and antisocial behavior, whereas moral disengagement was directly and indirectly related with antisocial behavior. Overall, these findings reflected substantial evidence from the literature on self-determination theory that autonomysupportive motivational climates are important environmental influences for need satisfaction, and are important correlates of prosocial behavior in sport, whereas controlling coach and teammate climates, along with moral disengagement, were important correlates of antisocial behavior in sport.